2011
DOI: 10.1186/1475-9276-10-34
|View full text |Cite
|
Sign up to set email alerts
|

Health status convergence at the local level: empirical evidence from Austria

Abstract: IntroductionHealth is an important dimension of welfare comparisons across individuals, regions and states. Particularly from a long-term perspective, within-country convergence of the health status has rarely been investigated by applying methods well established in other scientific fields. In the following paper we study the relation between initial levels of the health status and its improvement at the local community level in Austria in the time period 1969-2004.MethodsWe use age standardized mortality rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 45 publications
(55 reference statements)
1
46
0
Order By: Relevance
“…Both within the United Kingdom (Boyle, Exeter, and Flowerdew 2004;Leyland 2004;Dorling 1997;Leyland 2004;Shaw et al 1999;, between provinces in Canada (Mustard, Derksen, and Black 1999;Manuel and Hockin 2000), and for the 2,068 counties in the United States (Ezzati et al 2008), a tendency from convergence in the past to divergence in the more recent past follows from the various studies; in New Zealand, recent divergence has been observed as well (Pearce and Dorling 2006). On the other hand, Gächter and Theurl (2011) observed continuing convergence in Austria. In addition, Valkonen (2001) observed clear differences between several European countries in the trend in regional differences.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Both within the United Kingdom (Boyle, Exeter, and Flowerdew 2004;Leyland 2004;Dorling 1997;Leyland 2004;Shaw et al 1999;, between provinces in Canada (Mustard, Derksen, and Black 1999;Manuel and Hockin 2000), and for the 2,068 counties in the United States (Ezzati et al 2008), a tendency from convergence in the past to divergence in the more recent past follows from the various studies; in New Zealand, recent divergence has been observed as well (Pearce and Dorling 2006). On the other hand, Gächter and Theurl (2011) observed continuing convergence in Austria. In addition, Valkonen (2001) observed clear differences between several European countries in the trend in regional differences.…”
Section: Introductionmentioning
confidence: 98%
“…Valkonen (2001) also stressed the need for systematic studies on the trends in differential mortality, including mortality by region. Convergence of health due to diminishing returns of increases in health expenditures, improvement of education, and economic development is to be expected (Gächter and Theurl 2011). By contrast, divergence may occur due to the 'Matthew effect': regions with high life expectancy may experience even faster improvements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies also suggested such resurgence led to a recent setback in convergence of life expectancy at birth across the countries worldwide. This is also mainly attributable to unequal progress of public health outcomes across the world countries McMichael et al, 2004;Becker et al, 2005;Moser et al, 2005;Bloom and Canning, 2007;Dorius, 2008Dorius, , 2010Clark, 2011;Gächter and Engelbert, 2011). However, there are no studies across the world or in India, which focused on transition in maternal and child health care and outcome indicators.…”
Section: Health Transition and Convergencementioning
confidence: 99%
“…Few studies also suggested recent setbacks in convergence of life expectancy at birth across the countries worldwide McMichael et al, 2004;Becker et al, 2005;Moser et al 2005;Bloom and Canning, 2009, Dorius, 2008Clark, 2011;Gächter and Engelbert, 2011). The expectation that emerged in the 1960s and 1970s of the world gains in LEB does not guarantee convergence in population health status by a general deterministic process (McMichael et al, 2004).…”
Section: Introductionmentioning
confidence: 99%